The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.est.9b01795
|View full text |Cite
|
Sign up to set email alerts
|

Solid and Aqueous Speciation of Yttrium in Passive Remediation Systems of Acid Mine Drainage

Abstract: Yttrium belongs to the rare earth elements (REE) together with lanthanides and scandium. REE are commonly used in modern technologies, and their limited supply has made it necessary to look for new alternative resources. Acid mine drainage (AMD) is a potential resource since is moderately enriched in REE. In fact, in passive remediation systems, which are implemented to minimize the environmental impacts of AMD, REE are mainly retained in basaluminite, an aluminum hydroxysulfate precipitate. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 50 publications
(127 reference statements)
1
2
0
Order By: Relevance
“…From the experimental values, (Lozano et al, 2019a) proposed a value of n = 1 (monodentate complexes). This result is in agreement with the formation of a monodentate inner sphere complex of the YSO 4 + aqueous species and basaluminite surface, suggested by Extended X-ray absorption fine structure (EXAFS) and high-energy X-ray scattering (HEXS) (Lozano et al, 2019b). Scandium speciation differed from the rest of the REE, and bidentate surface complexes with ScSO 4 + and ScOH 2+ were proposed.…”
Section: Surface Complexation Modelingsupporting
confidence: 87%
“…From the experimental values, (Lozano et al, 2019a) proposed a value of n = 1 (monodentate complexes). This result is in agreement with the formation of a monodentate inner sphere complex of the YSO 4 + aqueous species and basaluminite surface, suggested by Extended X-ray absorption fine structure (EXAFS) and high-energy X-ray scattering (HEXS) (Lozano et al, 2019b). Scandium speciation differed from the rest of the REE, and bidentate surface complexes with ScSO 4 + and ScOH 2+ were proposed.…”
Section: Surface Complexation Modelingsupporting
confidence: 87%
“…The peak at ~2.4 Å matches well the distance between a central calcium ion and oxygen in the first coordination shell, while the broad correlation at ~6.1 Å can be tentatively attributed to interatomic distances to higher-order water coordination shells around the amorphous particles, as reported before for other nanoparticle systems 55 and ion pairs. 56 This suggests that the pair distribution function observed experimentally for frame cluster 300-369 is actually a combination of an already crystalline phase (which dominates the high-r part) and an amorphous (nano)precipitate, whose ordering does not extend beyond ~1 nm. Following the same logic, the measured PDF of the frame cluster 200-299 can be interpreted as a combination of contributions from a predominant disordered phase and a minor amount of a crystalline component.…”
Section: Nucleation Of Portlandite In the Absence Of Additivesmentioning
confidence: 94%
“…In contrast with our work which identified second shell Y−Si inner-sphere complexation, EXAFS analysis by Borst et al 75 indicated that Y retains a full hydration sphere when adsorbed to kaolinite and is present as an outer-sphere complex, and the absence of Y−Al and Y−Si suggested a lack of inner-sphere complexation. Inner-sphere REE complexes have been found for other media including bacteria (Pantoea agglomerans), 42 basaluminite from an AMDaffected environment, 79 and Fe and Mn oxyhydroxides. 80 At higher pH and ionic strength, desolvation of REE ions can lead to inner-sphere complexes forming on either aluminol (Al−OH) or siloxane (Si−O−Si) surfaces or terminal OH ligands.…”
Section: Synchrotron Xasmentioning
confidence: 99%